The futures for regenerative agriculture: insights from the organic movement and the tussle with industrial agriculture - Mambo, Tatenda; Lhermie, Guillaume (Frontiers in Sustainable Food Systems, 2024)
Concern has been raised about the potential greenwashing/co-optation of regenerative agriculture (RA) due to a lack of consensus on its definition. While the academic literature has cataloged various approaches to defining RA, each definitional approach carries with it a relative concern for its likelihood for co-optation and the potential transformative power it can have within the sector. As the industrial agrifoods sector is taking interest in the field, lessons from the organic movement are worth highlighting. The corporate system has easily integrated the foundational pillar of growing food without chemicals, but left behind the pillars of alternative food distribution, and a focus on whole foods and unprocessed ingredients. Corporate interest in RA could be a major driver for scaled adaptation, yet it may lose its focus on the regeneration of agriculture resources, ecosystems functions, and the social systems required to reproduce the next generation of farmers. The greatest challenge is that the fundamental concern is a philosophical one, which entails a shift in how humans perceive the natural world and their role in it. As RA scales, will it hold to its values and remain obscure, or could its values merge with the predominant industrial system to have significance and affect real change in agriculture?